Conflict Management and Decision-making Styles of Faculty Members of a Higher Education Insitution in Laguna Province, Philippines - Melodillar, Carla (Silliman Journal, 2025)
Conflicts in higher education institutions (HEIs) are common due to the interaction of diverse groups of people; therefore, conflict management is an essential activity to ensure that various HEI functions are performed effectively. Using a mixed-methods research design, the study showed that the most common source of conflicts in the HEI is task-related conflicts. In dealing with conflicts with subordinates, the majority of faculty members applied Integrating and Obliging conflict management styles, and fewer used Dominating or Compromising styles. In terms of decision-making, the majority of faculty members were rational and independent decisionmakers. Guided by the Dual Concern Theory and Choice Theory, it can be concluded that respondents tend to have a higher concern for their subordinates than for themselves when dealing with conflicts. Moreover, the infrequent occurrence of relationship-related conflicts in the HEI indicated that the respondents had a higher need for love and belongingness than for power, as they placed importance on relationships. It is further concluded that conflict management and decision-making styles are not zero-sum; each person can choose and control their responses depending on what the situation requires. Activities that foster relationship-building among faculty members in the HEI, as well as capacity-building initiatives to enhance problem-solving skills, are hereby recommended.